Evaluating scale and technical efficiency among farms and ranches with a local market orientation. Issue 3 (21st December 2017) - Bauman, Allison; Thilmany, Dawn; Jablonski, Becca B.R.
Abstract: In recent years, the growth in local food marketing channels has been significant. Most of the research in this field examining the economic implication of these trends has focused post-farmgate including supply chain analysis (e.g., Hardesty et al., 2014; King et al., 2010), regional economic impacts (e.g., Brown et al., 2014; Hughes et al., 2008; Jablonski et al., 2016) and consumer values and motivations that have driven demand (e.g., Costanigro, 2014; Lusk and Briggeman, 2009). To date, with the exception of a few case studies examining expenses and sales by channel assessment (LeRoux et al., 2010; Hardesty and Leff, 2010; Jablonski and Schmit, 2016) there has been little research that examines the impact on financial viability among farms selling through these markets. The goal of this paper is twofold: first, to identify the factors that have the greatest influence on the efficiency of farmers and ranchers that participate in local food systems, and second, to estimate the relationship between marketing strategy and farm financial efficiency, with a particular focus on variations across farm size. Our estimation of the stochastic production frontier suggests that scale, production enterprise specialty, market outlet choices, land ownership, and management of expenses have the greatest influence on producer financial efficiency. Our model suggests that scale has the largest impact on financial efficiency, providing evidence that, all else constant, the most important factor in the efficiency of direct market producers is scale. When profit is defined as operating profit, results indicate that marketing channel is not an important indicator of efficiency. But when profit is defined as return on assets, marketing channel is an important indicator of efficiency, albeit less than is scale. Results from this analysis indicate there are economies of scale associated with farms and ranches that sell through local and regional markets, and that scale rather than marketing channel has the largest influence on efficiency.